2013
DOI: 10.1063/1.4790571
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Structure, formation, and equilibration of ensembles of Ag-S complexes on an Ag surface

Abstract: We have utilized conditions of very low temperature (4.7 K) and very low sulfur coverage to isolate and identify Ag-S complexes that exist on the Ag(111) surface. The experimental conditions are such that the complexes form at temperatures above the temperature of observation. These complexes can be regarded as polymeric chains of varying length, with an Ag4S pyramid at the core of each monomeric unit. Steps may catalyze the formation of the chains and this mechanism may be reflected in the chain length distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…30 At very low θ S and at 5 K, S-Ag complexes existed on Ag(111) terraces, both in the form of individual units and concatenated chains. The steps were modified by S adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…30 At very low θ S and at 5 K, S-Ag complexes existed on Ag(111) terraces, both in the form of individual units and concatenated chains. The steps were modified by S adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…All STM imaging was done at 5 K in vacuum, at a pressure lower than 2.5 x 10 -11 Torr [17]. Assessment of the sulfur coverage, θ S , [the ratio of S atoms to Cu atoms in the (111) plane] was guided by the prior observation that a honeycomb-like reconstruction first appears at θ S ~ 0.05 [18,19].…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Elsewhere, we have reported that (near-)linear S-M-S units are structural motifs of complexes that form between S and coinage metals M on the Cu(111), Ag(111), and Au(100) surfaces. 16,18,20,51,52 In the case of CuS 2 complexes, we showed that the linear geometry was favored because it maximized the overlap between S porbitals and Cu-d z 2 orbitals. 20 The linearity of X-M-X units may provide an explanation for the different relative stabilities of R-A2 for O and S. In the double-row structures, there is an interaction ∆ between adsorbates, based on the fact that µ O of the double-row is always different than the average of the constituent single-row structures.…”
Section: Discussionmentioning
confidence: 80%